Meningkatkan hasil belajar menggunakan metode mind mapping - Amini, Siti Aisyah; Gustiawati, Syarifah; Basri, Samsul (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2025)
The low learning outcomes of students in the Fiqh subject at MTs Negeri Kota Bogor, particularly in the topic of halal and haram food and beverages, highlight the need to improve the quality of learning. This study aims to enhance students’ learning outcomes and active participation through the application of the Mind Mapping method. The research employed a Classroom Action Research (CAR) approach using the Kemmis and McTaggart model, which consists of four stages: planning, action, observation, and reflection. The study was conducted in two cycles involving 32 students of class VIII-B and one Fiqh subject teacher. Data were collected through observation sheets and achievement tests. The findings revealed a significant increase in student performance. In the pre-cycle stage, only 12.5% of students achieved the minimum passing grade. After implementing the Mind Mapping method, this figure rose to 68.75% in the first cycle and 96.8% in the second cycle. The average score also increased from 63 to 89. The results conclude that the Mind Mapping method is effective in improving students’ understanding and learning outcomes, as well as promoting greater engagement in Fiqh learning. Abstrak Rendahnya hasil belajar siswa pada mata pelajaran Fikih di MTs Negeri Kota Bogor, khususnya pada materi makanan dan minuman halal dan haram, menjadi perhatian penting dalam peningkatan kualitas pembelajaran. Penelitian ini bertujuan untuk meningkatkan hasil belajar dan partisipasi aktif siswa melalui penerapan metode Mind Mapping. Metode yang digunakan adalah Penelitian Tindakan Kelas (PTK) model Kemmis dan Mc. Taggart yang dilaksanakan dalam dua siklus. Subjek penelitian adalah 32 siswa kelas VIII-B dan satu orang guru mata pelajaran Fikih. Instrumen pengumpulan data meliputi observasi dan tes hasil belajar. Hasil penelitian menunjukkan peningkatan signifikan pada capaian belajar siswa. Pada pra-siklus, hanya 12,5% siswa yang mencapai ketuntasan. Setelah penerapan metode Mind Mapping, ketuntasan meningkat menjadi 68,75% pada siklus I dan mencapai 96,8% pada siklus II. Rata-rata nilai siswa juga meningkat dari 63 menjadi 89. Simpulan dari penelitian ini adalah bahwa metode Mind Mapping terbukti efektif dalam meningkatkan hasil belajar siswa serta mendorong keterlibatan aktif mereka dalam proses pembelajaran Fikih.